2016
DOI: 10.1155/2016/2343691
|View full text |Cite
|
Sign up to set email alerts
|

Adult ADHD Medications and Their Cardiovascular Implications

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a chronic neurobiological disorder exhibited by difficulty maintaining attention, as well as hyperactivity and impulsive behavior. Central nervous system (CNS) stimulants are the first line of treatment for ADHD. With the increase in number of adults on CNS stimulants, the question that arises is how well do we understand the long-term cardiovascular effects of these drugs. There has been increasing concern that adults with ADHD are at greater risk for develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Furthermore, known common side effects associated with stimulants described in the literature include tachycardia, arrhythmias, and blood pressure elevation. 49 The 300% increases in risk for arrhythmias at 30 days (HR, 3.0; 95% CI, 1.1-8.7) and 180 days (HR, 3.0; 95% CI, 1.4-6.4) identified in this study support these literature findings. 50 On the other hand, our finding that there was no statistically significant increase in CV risk long term contradicts the anticipated hypothesis based on findings from a meta-analysis of 10 randomized, placebo-controlled trials of CNS stimulants that found a statistically significant increased resting heart rate with these stimulants (increase of 5.7 bpm; 95% CI, 3.6-7.8 bpm) and systolic blood pressure (increase of 2.0 mm Hg; 95% CI, 0.8-3.2 mm Hg).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, known common side effects associated with stimulants described in the literature include tachycardia, arrhythmias, and blood pressure elevation. 49 The 300% increases in risk for arrhythmias at 30 days (HR, 3.0; 95% CI, 1.1-8.7) and 180 days (HR, 3.0; 95% CI, 1.4-6.4) identified in this study support these literature findings. 50 On the other hand, our finding that there was no statistically significant increase in CV risk long term contradicts the anticipated hypothesis based on findings from a meta-analysis of 10 randomized, placebo-controlled trials of CNS stimulants that found a statistically significant increased resting heart rate with these stimulants (increase of 5.7 bpm; 95% CI, 3.6-7.8 bpm) and systolic blood pressure (increase of 2.0 mm Hg; 95% CI, 0.8-3.2 mm Hg).…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, known common side effects associated with stimulants described in the literature include tachycardia, arrhythmias, and blood pressure elevation. 49 The 300% increases in risk for arrhythmias at 30 days (HR, 3.0; 95% CI, 1.1-8.7) and 180 days (HR, 3.0; 95% CI, 1.4-6.4)…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…For example, it can be difficult to disentangle the cause and therefore access to appropriate diagnoses/support for issues like poor working memory ("brain fog"), which is common with ADHD/ADHC, as it is for chronic inflammatory conditions like arthritis or lupus (Mackay, 2015). For ADHD/ADHC individuals with heart conditions, it can be harder to manage their ADHD/ADHC where often the first line of treatment is stimulant medication, due to increased risk of heart problems (Sinha et al, 2016). For neurodivergent individuals experiencing a flare up in their chronic illness (e.g., increased pain and/or fatigue and brain fog), it can further exacerbate executive functioning issues already present with their neurodivergent condition.…”
Section: Intersection Of Neurodivergence and Co-occurring Disabilitiesmentioning
confidence: 99%
“…Another risk factor to consider in this case report is the patient’s morbid obesity (BMI: 69.81) with a relationship with new-onset atrial fibrillation. Although some case reports suggest a relationship between amphetamine use and new-onset atrial fibrillation, this patient had several other independent risk factors for new-onset atrial fibrillation [ 14 - 15 ]. Obese individuals have a 49% increased risk of developing atrial fibrillation as compared to non-obese individuals, with a positive correlation between increasing BMI and risk of developing atrial fibrillation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%